PERANAN ORANGTUA DAN GURU SEBAGAI PENDIDIK DALAM MEMBENTUK KARAKTER ANAK - Hamdi Abdillah (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
The character of a child is a personality quality that includes morals and morals that can be formed by the nature of birth, family, and the environment in which to grow and become a special characteristic that distinguishes it from others. Someone with character will have more advantages than others. Excellence in good self-character can lead to life achievements. Someone's achievement is an achievement and is a proof of self quality. The quality of one's self will be shaped and built on the basis of the values of the character he does. Self character is the development of character values as a foundation for behavior in society. Diverse character values, if implemented in everyday life will certainly make someone have more value and quality. Parental teacher and parental deterrence will grow the character of the child, meaning that the character of the child will be formed by the example of the teacher and parent who synergize with each other